Analisis Sensori Manisan Jahe Merah (Zingiber Officinale Var. Rubrum) - Ruri Wijayanti; Arsan Arsan (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2023)
The purpose of this study was to determine the most preferred concentration of palm sugar and granulated sugar based on organoleptic tests. A food assessment method that uses the five senses is an organoleptic assessment and is generally called a sensory test. The results showed that the most preferred candied red ginger with the addition of palm sugar and granulated sugar was treatment E (added 40% palm sugar and 60% granulated sugar) with a preference value for taste 3.40 (like), aroma 3.72 (like ) and texture 3.56 (like) on a rating scale of 5.